1998
DOI: 10.1016/s0002-9440(10)65593-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of p27Kip1 and Cyclin-Dependent Kinase 2 in the Proliferation of Non-Small Cell Lung Cancer

Abstract: The cell cycle is governed by a family of cyclin-dependent kinases (Cdks). Cdk2 forms a functional complex with cyclin E and plays a pivotal role in the regulation of G1/S transition. Cdk2 activity is negatively regulated by interactions with inhibitors. p27 Kip1 , one of the most potent inhibitors of Cdk2, was recently identified as a powerful negative prognostic marker in non-small cell lung cancer as well as in colorectal and breast cancer. In the present study, the expression of p27 and Ki-67 antigen in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
61
2
2

Year Published

1999
1999
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 35 publications
(29 reference statements)
6
61
2
2
Order By: Relevance
“…Alterations in p27 Kip1 warrant particular attention as p27 Kip1 protein levels are reduced in several types of cancer including melanoma (Catzavelos et al, 1997;Loda et al, 1997;Mori et al, 1997;Florenes et al, 1998;Kawana et al, 1998), and p27 Kip1 heterozygous mice are prone to induced tumor formation (Fero et al, 1998). B-RAF is mutated in approximately 70% of melanomas (Davies et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in p27 Kip1 warrant particular attention as p27 Kip1 protein levels are reduced in several types of cancer including melanoma (Catzavelos et al, 1997;Loda et al, 1997;Mori et al, 1997;Florenes et al, 1998;Kawana et al, 1998), and p27 Kip1 heterozygous mice are prone to induced tumor formation (Fero et al, 1998). B-RAF is mutated in approximately 70% of melanomas (Davies et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…p27 Kip1 protein blocks progression from the G1 to the S phase of the cell cycle and is highly expressed in cells arrested at the G0 or G1 phase (2)(3)(4). Recent reports have indicated that expression of p27 Kip1 protein is inversely related to proliferative activity (as measured using Ki-67 antibody) in cells at all stages except the G0 phase in non-small-cell lung carcinomas, endocrine tumors, and malignant lymphomas (25)(26)(27). In the present study, no correlation was found between the expression of p27 Kip1 protein and the proliferative activity measured using PCNA antibody, which reacts with nuclei in the late G1 and S phases of the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the low levels of p27 protein that have been observed in many human cancers are due to enhanced proteolysis [47][48][49][50][51][52]. This suggested that proteins involved in p27 degradation may have oncogenic properties (see Fig.…”
Section: P27 and Human Cancersmentioning
confidence: 99%